Kinematic Analysis of the Tram-pedestrian Collision - a Preliminary Case Study. - Tomsovsky, Lubos; Kubovy, Petr; Lopot, Frantisek; Jelen, Karel (Manufacturing Technology Journal, 2022)
The goal of the study was to conduct a preliminary analysis of the kinematics of tram-pedestrian collision in case of a side impact. A T6A5-type tram, traveling at the speed of 10 km/h, was used for the crash analysis and reconstruction of the collision. The pedestrian response was analyzed using a crash-test dummy. For the purpose of this study, the postimpact dummy movement was approximated by the motion of its center of mass (COM) and only the translation movement in the frontal plane of the dummy (along the horizontal and vertical axes) was considered. The results showed a significant change in the coefficient of restitution after the initial impact. At first, the coefficient of restitution was high (e = 0.94), suggesting an almost perfectly elastic collision, followed by a sharp decrease (e = 0.07) within a short period of time (t = 0.02 s) that suggested an almost perfectly inelastic collision. After that, the coefficient of restitution reached a plateau phase with the values ranging from 0.18 to 0.32 and corresponding to a percentage loss of kinetic energy falling within 89 % and 97 %. The preliminary analysis of this study highlighted some features of side-impact tram-pedestrian collision and its kinematics.
Keywords: Tram; Pedestrian; Collision; Coefficient of restitution; Safety.